Assessment of Pharmacokinetic Interactions of the HCV Ns5A Replication Complex Inhibitor Daclatasvir with Antiretroviral Agents: Ritonavir-Boosted Atazanavir, Efavirenz and Tenofovir. Issue 7 (October 2013) - Bifano, Marc; Hwang, Carey; Oosterhuis, Berend; Hartstra, Jan; Grasela, Dennis; Tiessen, Renger; Velinova-Donga, Maria; Kandoussi, Hamza; Sevinsky, Heather; Bertz, Richard
Background: Approximately one-third of all HIV-infected individuals are coinfected with HCV, many of whom will receive concomitant treatment for both infections. With the advent of direct-acting antivirals (DAAs) for HCV, potential drug interactions between antiretrovirals and DAAs require evaluation prior to co-therapy. Methods: Three open-label studies were conducted in healthy subjects to assess potential interactions between the investigational first-in-class HCV NS5A replication complex inhibitor daclatasvir and representative antiretrovirals atazanavir/ritonavir, efavirenz and tenofovir disoproxil fumarate. Results: Target exposure was that of 60 mg daclatasvir alone. Dose-normalized (60 mg) geometric mean ratios of daclatasvir AUCτ for 20 mg ± atazanavir/ritonavir (2.10 [90% CI 1.95, 2.26]) and 120 mg ± efavirenz (0.68 [0.60, 0.78]) showed less than the three-fold elevation and two-fold reduction, respectively, in systemic exposure predicted by prior interaction studies with potent inhibitors/inducers of CYP3A4. Daclatasvir dose adjustment to 30 mg once daily with atazanavir/ritonavir and 90 mg once daily with efavirenz is predicted to normalize AUCτ relative to the target exposure (geometric mean ratios 1.05 [0.98, 1.13] and 1.03 [0.90, 1.16], respectively). Atazanavir exposure (Cmax, AUCτ and C24 trough) and efavirenz Ctrough under coadministration were similar to historical data without daclatasvir. No clinically relevant interactions between daclatasvir and tenofovir disoproxil fumarate were observed for either drug, and no dosing adjustments were indicated. Daclatasvir was well tolerated in all three studies. Conclusions: The pharmacokinetic data support coadministration of daclatasvir with atazanavir/ritonavir, efavirenz and/or tenofovir. A Phase III study in HIV–HCV coinfection has commenced using the described dose modifications.